IMPLEMENTASI KEBIJAKAN PROGRAM PENINGKATAN KINERJA PEGAWAI PADA BIDANG PEMASARAN DINAS PARIWISATA DAN EKONOMI KREATIF PROVINSI SULAWESI TENGAH - Syachrinaldy, Syachrinaldy (Katalogis, 2016)
The purpose of this study that to be achieved was to determine and analyze the implementation of Employee Performance Enhancement Policy at the Marketing Division of Middle Sulawesi Tourism and Creative Economy Department. The research method used was qualitative method. In this study, there were several informants who understand the issues examined, while the so-called informants here were as follows: Secretary of Central Sulawesi Tourism and Creative Economy Department, Head of Marketing Division, and Marketing Staff. The types of data used were primary and secondary data. The data collection was done by means of observations, interviews, and documentations. Based on this study, the researcher suggested several results: Communication was one of the main factors in policy implementation. Communication became the main line to the execution of any program. Human resources were the main factors that must be owned by any particular institution or unit, both governmental and non-governmental institutions. Vice versa if the perspectives of the implementers were different with the decision makers, the process of policy implementation became increasingly difficult. In such cases, the implementers would use discretions and sometimes subtle ways to inhibit, or would gain individual benefit of each in the process of policy implementation.